POWER SOURCES AND DYNAMICS OF GROUNDWATER LEVELS ON THE RIGHT BANK OF THE KYIV RESERVOIR - Kuzmenko, E.; Davybida, L.; Zinchenko, V.; Nikitash, A.; Yakovlev, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Relevance of the research was determined by the necessity of studying the dynamics of soil water content depending on the temporal variability of hydrogeological and geotechnical characteristics. In turn, the study of the characteristics is necessary for hydrogeological calculations related to evaluation of groundwater treatment, and for determining the prospects for development and activation of exogenous geological processes. This paper presents results of investigation of the hydrogeological and geotechnical conditions within natural boundary of Mezhyhirya which is located on the right bank of the Kyiv hydroelectric reservoir on the Dnieper. The power sources of the aquifers were identified on the basis of information analysis that was obtained by the study of groundwater level regime. It was revealed that the shaping of the groundwater levels regime was carried out by the rainfall infiltration in the aquifer directly on the site, the infiltration of precipitation in the adjacent areas and further transit on the territory, the transit from the reservoir of the Kyiv pumped-storage. It was proved that in the annual cycle the levels regime and the variability of rainfall are in close correlation with the time lags of levels in the magnitude of 1.2 to 4 months. Dependencies of the levels time lags in relation to precipitations were identified. The dependencies are shown in the reduction of time lags approaching to the groundwater discharge zone and in a direct correlation between the lags and altitudes of the levels in the same direction and, therefore, in inverse correlation with the power of the aeration zone. The basis of the input data has been generated for further research and integrated assessment of landslide hazards within the territory near the slopes.
Keywords: groundwater levels; precipitation; hydrogeological regime; observation wells; irrigation factors; correlation analysis